A legal study on the child's custody upon one of the parent conversion in Malaysia / Nik Nurus Amilin Nik Jallalluddin ...[et al.] - Nik Jallalluddin, Nik Nurus Amilin; Mohd Lutfi, Nursyathirah; Mahasan, Salwani; Idris, Roslina (2010)
Nowadays, the right of child custody after one of his or parent converted into Islam becomes a critical and conflict issue between Muslim and non-Muslim party. Till now, it cannot be resolved. Most cases are decided in favour of mother. What about the right of father? Is it should be ignored? The existing statutes or laws regulating the child custody are still not enough and should be amended to provide justice for both parties. What about the right of the child? Should it be taken into consideration too? Both Syariah and Civil Court could not intervene each other as they have their own jurisdiction provided under the Federal Constitution. It was limited for both parties to grant the right of custody as it was still vigorous. How it should be determined and solved? That is why this research will be conducted where to find out what are the basis of the problem and its solution to grab. We will look forward Civil and Syariah law perspectives.